Isa Genzken 1992 - 2003 : Ausstellungen, Arbeiten, Werkverzeichnis = Exhibitions, Works, Catalogue raisonné. - Diederichsen, Diedrich; Genzken, Isa; Loers, Veit; Müller, Vanessa Joan; Ruf, Beatrix; Strau, Josef; Tillmans, Wolfgang (Köln : Verlag der Buchhandlung Walther König Köln, 2003)
The works by Isa Genzken have been exhibited in international institutions and galleries for over twenty years. Her work is characterized by a variety of often unexpected materials. Her artistic vocabulary acknowledges modernism as both model and loss, reflecting an awareness of art's present horizon. This book offers a survey that allows the seeming discontinuities in Isa Genzken's work to appear as a complex continuum. It is a sequel to the first part of the catalogue raisonné Jeder braucht mindestens ein Fenster (Verlag der Buchhandlung Walther König, Köln, 1992).
bibliog. p. 188-191
biog., ind. tent., gr. tent. p. 187
Duits
Engels
Exhibition. Isa Genzken 1992 - 2003 (1). Exhibition. Isa Genzken 1992 - 2003 (2). Kunsthalle Zürich. Museum Abteiberg Mönchengladbach. 2002-09-22. 2003-03-22. 2003-01-05. 2003-05-25
boek
Keywords: Genzken, Isa